effect of glycemic control and hypertension on serum basic amino acids in type II diabetes mellitus - Al-shamma, ghassan; AL-Bazzaz, Abaul Rahman A.; Asker, Faiz K.; Numan, Mohammed (Journal of the Faculty of Medicine Baghdad, 2005)
Background: